MODELING DISPERSI EMISI BAU GAS SO2 DARI CEROBONG INDUSTRI TEKSTIL - Prayudi, Teguh (BPPT)
Textile Industry gives economic and fi nancial contribution to society, however it has negative impact to the environment, i.e. air pollution, bad smell and noise. For that reason, a study to evaluate exhaust gas emission of some industry textile was carried out from the stack. The aim of the study is to abtain SO2 gas concentration, which is emited from the stack A gas dispersion anlysis, it was indicated that SO2 gas concentration from the stack is still below the standard (1200 mg/m3). Thehighest SO2 concentration was 18 mg/m3 at about 200 meter away from the stack. It meant that SO2 concentration and SO2 odor from the textile industry did not give any impact to the environmentKey words: emission, textile industry,